Internet connectivity disruption in Syria (Syria) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Syria. Data sourced from IODA.
Network Disruption Incident ID: SY-2026-0053. Severity: critical. Confidence: 75%